The Effect Of Brand Awareness And Trust On Customer Brand Loyalty Of Wardah Products In Banten Province - Muhamad Suhaemi (Ilomata International Journal of Management, 2021)
This research aims to know the influence of brand awareness and brand trust on customer brand loyalty Wardah in the Province of Banten, the simultaneous influence of both are also tested in this study. The population in this research is the customers Products in Banten Province. The research was carried out in June until August 2018. The method used is the sample election assidental sampling technique or the formula used hence theory Malhotra and produced 85 representative sample, a sample that is truly representative of the population. Data collection is carried out by means of questionnaires to spread 85 respondents. Based on the results of this research it can be concluded that variables brand awareness and confidence in the brand to brand loyalty either partial or simultaneous. The influence of brand awareness greater than trust the brand. And 76.3% wardah customer brand loyalty in Banten Province affected by the brand awareness and confidence in the brand, while the rest is influenced by other factors not examined.